Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 8 - Section 8.4 - Equations Quadratic in Form - Exercise Set - Page 635: 20



Work Step by Step

Since, $u^2-u-6=0$ Factorize the expression as follows: $(u-3)(u+2)=0$ or, $u=${$-2,3$} Replace $u$ with $x^{-1}$, we have $x^{-1}=-2 \implies \dfrac{1}{x}=-2$ $x=\dfrac{-1}{2}$ and $x^{-1}=3 \implies \dfrac{1}{x}=3$ $x=\dfrac{1}{3}$ Hence, our solution set is $x=${$\dfrac{-1}{2},\dfrac{1}{3}$}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.